Spatiotemporal Variation in the Catch Composition and Abundance of Precious Corals Around Taiwan: Implications for Fisheries Management - Chen, Chih-Shin (Frontiers in Marine Science, 2021)
Precious corals are a fishery resource of cultural and religious importance. Because of their high commercial value, precious corals have been exploited for several centuries in the Mediterranean and for almost one century in the Northwest Pacific. Taiwanese fishing fleets have harvested precious corals since the 1920s; however, management regulations have only been promulgated since January 2009. This study examined spatiotemporal variation in the catch composition and abundance of precious corals Corallium, Hemicorallium, and Pleurocorallium spp. around Taiwan using fishery data from 2009 to 2018 and discussed its implications for fisheries management. Licenses are issued for 60 vessels annually, and the annual total catch was 2.9–3.5 t between 2009 and 2018, peaking in 2015 and then decreasing sharply in 2016. Because of the use of non-selective fishing gear, dead and fossilized colonies were included in the total catches of the fishery. Fossilized colonies were predominant (average 78.5%) in the total catches, whereas the proportion of live colony catches accounted for less than 5%. Pink coral (Momo) was predominant in the total and live colony catches during the 10-year period. The Taiwanese precious coral fishing fleets are restricted to harvesting precious corals in five designated fishing grounds (DFGs; A–E). The fishing effort (vessel∙day) was mainly concentrated in DFG-A (average 56.6%), which accounted for an average of 63.9% of the total catches. However, the live colony catches were largest in DFG-E (average 39.9%) and DFG-A (average 39.6%). The annual catch rates of live colonies decreased in two major fishing grounds (DFGs-A and DFG-B), whereas it increased in two minor fishing grounds (DFGs-C and DFG-D). The temporal variation in occurrence rates of live colonies decreased between 2015 and 2018, indicating a declining trend for precious coral populations around Taiwan. These results indicate that an unsustainable condition may occur in the near future if the precious corals continue to be harvested at the current scale. Revised regulations for the Taiwanese precious coral fishery should contain proposals on fishing gear modifications, a rotational harvesting scheme, or both; such measures can contribute to the conservation of precious coral populations.